The Problems in Indonesian Language Teaching During the Covid-19 Pandemic - Hani Subakti; Eka Selvi Handayani (IAIN Bengkulu, 2022)
The rationale behind this study was the occurring problems in online teaching and learning of Indonesian during the Covid-19 pandemic. The purpose of this study was to investigate the problems in Indonesian teaching and learning during the Covid-19 pandemic at SD Negeri 02, North Samarinda in the 2020/2021 academic year. This study applied a qualitative approach. The instruments used were interviews and documentation. The results of the study showed that there were existing problems in Indonesian language teaching and learning during the Covid-19 pandemic at SD Negeri 023, North Samarinda in the 2020/2021 school year. The problems identified were mostly related to the students. First, they were reluctant to read Indonesian textbooks. Additionally, they spent more time playing at home. It was unfortunate since to understand Indonesian, students should read Indonesian language textbooks more frequently. Besides, parents share the responsibility to supervise and control their children to learn how to read textbooks on Indonesian. Therefore, well-organized cooperation among the classroom teachers, parents, and students is needed to minimalize the problems. Hence, Indonesian language teaching and learning will create better outcomes